Increased plasma DYRK1A with aging may protect against neurodegenerative diseases - Delabar, Jean M.; Lagarde, Julien; Fructuoso, Marta; Mohammad, Ammara; Bottlaender, Michel; Doran, Eric; Lott, Ira; Rivals, Isabelle; Schmitt, Frederic A.; Head, Elizabeth; Sarazin, Marie; Potier, Marie-Claude (Translational psychiatry, 2023)
Early markers are needed for more effective prevention of Alzheimer’s disease. We previously showed that individuals with Alzheimer’s disease have decreased plasma DYRK1A levels compared to controls. We assessed DYRK1A in the plasma of cognitively healthy elderly volunteers, individuals with either Alzheimer’s disease (AD), tauopathies or Down syndrome (DS), and in lymphoblastoids from individuals with DS. DYRK1A levels were inversely correlated with brain amyloid β burden in asymptomatic elderly individuals and AD patients. Low DYRK1A levels were also detected in patients with tauopathies. Individuals with DS had higher DYRK1A levels than controls, although levels were lower in individuals with DS and with dementia. These data suggest that plasma DYRK1A levels could be used for early detection of at risk individuals of AD and for early detection of AD. We hypothesize that lack of increase of DYRK1A at middle age (40–50 years) could be a warning before the cognitive decline, reflecting increased risk for AD.